Construcción de un rincón de lectura para el mejoramiento del aprendizaje en niños(as) de nivel medio de la escuela fiscal mixta Lauro Damerval Ayora n°2, de la ciudad de Loja, periodo 2014 – 2015 - Suárez Enriquez, María del Cisne (2015)
Galo Guerrero Jimenez (2011) manifest " not think it's an exaggeration to say that from reading a society builds a better world because it can reflect upon itself.". because reading is the act by which we enter visual trade with the word, and the word is the channel by which I will modify a famous sentence of Heidegger, reality makes us" . Therefore knowing the concept of reading, the reading process, the effectiveness and importance of reading corners in children ran the topic called: Construction of a reading corner for improving learning in children with a middle level of learning. Children are from the Fiscal school Damerval Laurel Ayora No. 2 in the city of Loja. Period 2014 – 2015. This was made under the provisions of Regulation Academic Board of the National University of Loja. The methods used for this research work were:Scientific, inductive deductive, analytic and synthetic statistical model, the same that formed the basis for making the research process efficiently. The techniques and instruments used were: Survey to students of second, third and fourth grade. Survey to parents of second, third and fourth grade, survey to teachers and survey to directors of the institution, data- directed reading children of second, third and fourth grade, tales assessment, evaluation of books reading, overall evaluative survey of the reading corner. Based on the investigation conducted, the following data is the conclusion: that 100% of students in second and fourth grade like reading, third grade students reading like 90%. 100% of students in second and fourth grade would like to have a reading corner in the classroom, while the third graders would like to have a reading corner 60%. 90% of parents of second and third degree like reading. According to the story it analyzed fir fourth grade with best score was 93.33%. According to these results cast 80% corresponds to hit fourth grade that is in direct relation to their high academic performance that is 9-10 overall. Further according to the data-reading students in fourth place individually welcomed by students have read more books 4.7 equivalent to five books. The data are very encouraging and may be the impetus for further research. Keywords: Reading, Learning, constructionism, education.